Systematic Review of Dangerous Goods Handling in Port Operations: Safety Management Systems, Risk Assessment, and Technological Innovations - Nugraha, Adelio Shatara; Azisah, Nur (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
The handling of dangerous goods in port environments represents one of the most critical safety challenges in maritime logistics, necessitating comprehensive risk management approaches and advanced safety protocols. This systematic literature review analyzes current practices, challenges, and innovations in dangerous goods handling at ports, examining safety management systems, risk assessment methodologies, and technological solutions. Following PRISMA guidelines, 37 peer-reviewed articles published between 2014-2024 were systematically analyzed based on their relevance to dangerous goods handling, port operations, safety management, and risk assessment in maritime environments. The analysis reveals five key themes: risk assessment and safety management systems, regulatory frameworks and compliance, technological innovations and automation, human factors and training, and environmental impact and sustainability. Major findings indicate that integrated risk-based approaches, combined with advanced detection capabilities and comprehensive training programs, significantly enhance safety outcomes in dangerous goods handling. The research emphasizes the critical need for holistic safety management systems that integrate technological solutions, regulatory compliance, human factor considerations, and environmental protection measures. Current evidence suggests that ports implementing comprehensive safety management frameworks demonstrate substantial improvements in incident reduction and operational efficiency. Future research directions should prioritize the development of smart port technologies, standardized international protocols for dangerous goods management, and enhanced integration between automated systems and human decision-making processes to address emerging challenges in increasingly complex port environments.